2021
DOI: 10.1007/s40122-021-00236-1
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Therapy for Treating Phantom Limb Pain Accompanied by Jumping Residual Limb: A Short Review and Case Study

Abstract: Phantom limb pain (PLP) is a common complaint among patients after amputation, while jumping residual limb is a rare post-amputation complication, they rarely happen at the same time and both remain difficult to manage. At present, there is a paucity of literature on this topic, and no treatment has been proven effective for treating both of them. In the present brief report, we described a patient who developed severe PLP accompanied by jumping residual limb after below-the-knee amputation and she was treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…[ 18 ] The analgesic effects of intrathecal midazolam have been explored in numerous studies with different patients and clinical conditions[ 27 ] covering one case study confirming the effectiveness of IV administration of midazolam in relieving limb pain during spinal anesthesia. [ 28 29 ] In addition, another study showed midazolam has analgesic effects similar to opioids and it could be effective in relieving limb pain. [ 30 ] As confirmed by some evidence, including Honarmand et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] The analgesic effects of intrathecal midazolam have been explored in numerous studies with different patients and clinical conditions[ 27 ] covering one case study confirming the effectiveness of IV administration of midazolam in relieving limb pain during spinal anesthesia. [ 28 29 ] In addition, another study showed midazolam has analgesic effects similar to opioids and it could be effective in relieving limb pain. [ 30 ] As confirmed by some evidence, including Honarmand et al .…”
Section: Discussionmentioning
confidence: 99%
“…"Jumpy stump syndrome" is defined by dystonic, choreiform, and myoclonic movements of the amputated limb. [2][3][4] These patients may also experience associated neuropathic pain, including phantom or residual limb pain. 3 While there is a detailed body of research regarding amputee-related pain conditions, our understanding of this movement disorder is limited to a few individual case studies.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] These patients may also experience associated neuropathic pain, including phantom or residual limb pain. 3 While there is a detailed body of research regarding amputee-related pain conditions, our understanding of this movement disorder is limited to a few individual case studies. It is believed that "jumpy stump syndrome" can begin shortly after initial amputation or years later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation